Nanostructured Light-Emitters - Nguyen, Hieu Pham Trung (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Significant progress has been made in nanophotonics and the use of nanostructured materials for optoelectronic devices, including light-emitting diodes (LEDs) and laser diodes, which have recently attracted considerable attention due to their unique geometry. Nanostructures in small dimensions, comprising nanowires, nanotubes, and nanoparticles, etc,. can be perfectly integrated into a variety of technological platforms, offering novel physical and chemical properties for high-performance, light-emitting devices. This Special Issue aims to present the most recent advances in the field of nanophotonics, which focuses on LEDs and laser diodes. We invite contributions of original research articles, as well as review articles that are aligned to the following topics that include, but are not limited to, thetheoretical calculation, synthesis, characterization, and application of such novel nanostructures for light-emitting devices. The application of nanostructured light-emitters in general lighting, imaging, and displays is also highly encouraged.